AJARAN UPEKSA MEMBENTUK KARAKTER SISWA PASCA PEMBELAJARAN DARING, KELAS V SD NEGERI 5 PENATIH KECAMATAN DENPASAR TIMUR T.A. 2021/2022 - I Ketut Winantra; I Komang Dedi Diana; I Putu Sukanta (WIDYANATYA, 2022)
ABSTRACT The character building of the student now has been the main focus of schools, especially during the Covid-19 pandemic. The teaching of Catur Paramita, especially Upeksa, 'the teachings of morality or ethics in respecting others' may be the basis for this view. This study was conducted to determine the application of Upeksa's teaching, obstacles, and implications in building the student character during post-online learning for fifth grade at SD Negeri 5 Penatih, East Denpasar District, Academic Year 2021/2022. This research applied the qualitative method. Based on the analysis, the Upeksa's teachings are actualized through the teachings of Tri Hita Karana, three harmonious balance relationships, namely with God, with fellow human beings, and the the natural environment. The obstacles in the application of the Upeksa's teachings are (1) internal factors (a) differences in the intelligence of students, (b) interest in learning, and (c) talent. (II) External factors which include (a) family environment, (b) school environment, and (c) community environment. Meanwhile, the implication is the occurrence of changes in attitudes in students such as (a) sradha and bhakti attitudes, (b) discipline, (c) caring, (d) responsibility, and (e) politeness. ABSTRAK Pembentukan karakter siswa sekarang ini menjadi fokus utama sekolah, terlebih di masa Pandemi Covid-19. Ajaran Catur Paramita khususnya Upeksa ‘ajaran susila atau etika dalam sikap menghargai orang lain’ menjadi dasar pandangan menuju arah tersebut. Penelitian ini dilaksanakan untuk mengetahui penerapan ajaran Upeksa, kendala-kendala, dan implikasinya dalam membentuk karakter siswa selama pembelajaran pasca daring kelas V SD Negeri 5 Penatih, Kecamatan Denpasar Timur Tahun Ajaran 2021/2022. Penelitian ini berbentuk metode kualitatif. Berdasarkan analisis, ajaran Upeksa diaktualisasikan melalui ajaran Tri Hita Karana, tiga hubungan keseimbangan yang harmonis yaitu dengan Tuhan, sesama manusia, dan alam lingkungan. Kendala dalam penerapan ajaran Upeksa adalah (1) faktor internal (a) perbedaan kecerdasan peserta didik, (b) minat belajar, dan (c) bakat. (II) Faktor eksternal yang meliputi (a) lingkungan keluarga, (b) lingkungan sekolah, dan (c) lingkungan masyarakat. Sedangkan, implikasinya adalah terjadinya perubahan sikap pada diri siswa seperti (a) sikap sradha dan bhakti, (b) kedisiplinan, (c) kepedulian, (d) tanggung jawab, serta (e) sikap sopan santun.